G.N. Speransky — the founder and the head of the first State Scientific Institute of Maternity and Infancy Protection (to the 140th anniversary) - A. A. Baranov; V. Yu. Al'bitskii; S. A. Sher (Вопросы современной педиатрии, 2013)
The article contains the data received during the study of archival documents, collected articles of the Institute of Pediatrics of the Academy of Medical Sciences of USSR, pediatric journals and scientific works of G.N. Speransky — the founder and the head of the first State Scientific Institute of Maternity and Infancy Protection (MIP) in pre-revolutionary Russia at the 20–30 years of the 20th century. G.N. Speransky was the first director of the MIP, as well as the chief of therapeutic department of the institute and the head of the chair of infancy disorders. His excellent organizational and high professional qualities contribute to the formation of the Soviet system of the MIP, development of pediatric science and decrease of the high level of infantile morbidity in our country.